Geomorphological Features in the AL- Tilil Valley Basin Northeastern Maysan Governorate - Mishary Mohammad Gabr Al-Kinani, Duaa; أ.د حسين عذاب خليف الموسويّ (Journal of College of Education, 2022)
Abstract     The research aims to study the landforms in the AL Tilil Valley Basin Northeastern Maysan Governorate, which is located astronomically between latitudes (32⸰41-39= - 32⸰58-16=) to the north and longitudes (46⸰38-45= - 46⸰ 51- 6.9 =) in the east, and geographically, it is located in the southeastern part of Iraq and in the northeastern part of Maysan governorate within the western Ali district of Maysan governorate. To the southeast is the Jefta Valley Basin. The area of   the basin is (206.33) km2, and the total length of the basin is (55.15) km. In determining the landforms in the region, the study relied on a geological field survey and a digital and visual analysis of topographical maps, satellite visuals and aerial photos, and the landforms were classified.  In the region, it is divided into five land units, which are: units of structural origin - erosion, including (Cuesta, Hogback), units of erosion origin, including (Badlands, Valleys), units of sedimentary origin (Flood Plains, Alluvial Fans, valley Bed Deposits), units of wind origin, as well as Land Forms of Man Made
Keywords: : (AL- Tilil Valley , Land Units , Geomorphological Map)